Bivalvia biostratigraphy of Aksütlü region (Hekimhan, NW Malatya, Türkiye) and paleoclimatological interpretations - Müjde Gürsoy (Bulletin of the Mineral Research and Exploration)
In this study, Early Miocene bivalve fauna obtained from Hekimhan Aksütlü locality is presented. Abundant and well-preserved ostreid samples are interesting in the area where molluscs have notbeen studied before. Within the community where ostreids are dominant, eight species have been identified; four species of the Ostreoidea, two Pectinoidea, one Arcoidea and one Cardioidea havebeen recorded. The Carbon (13C/12C) and Oxygen (18O/16O) isotope ratio results of the ostreids and sediments indicate the first findings related to the Miocene Climate Optimum (MCO) Event inAnatolia. Identified bivalves reveal that Akyar Formation was deposited in a shallow and warm sea in Early Miocene.